2022
DOI: 10.1186/s12859-021-04534-5
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical relation extraction via knowledge-enhanced reading comprehension

Abstract: Background In biomedical research, chemical and disease relation extraction from unstructured biomedical literature is an essential task. Effective context understanding and knowledge integration are two main research problems in this task. Most work of relation extraction focuses on classification for entity mention pairs. Inspired by the effectiveness of machine reading comprehension (RC) in the respect of context understanding, solving biomedical relation extraction with the RC framework at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They also demonstrated the crucial role of syntax in transfer learning [ 27 ]. Biotian et al [ 28 ] reported another similar study. They revealed that open-domain reading comprehension data and knowledge representation could help to improve biomedical relation extraction.…”
Section: Related Workmentioning
confidence: 76%
“…They also demonstrated the crucial role of syntax in transfer learning [ 27 ]. Biotian et al [ 28 ] reported another similar study. They revealed that open-domain reading comprehension data and knowledge representation could help to improve biomedical relation extraction.…”
Section: Related Workmentioning
confidence: 76%
“…[ 19 , 63 ]. CTD KB 9 has been extensively used in projects where the association between biomedical entities plays an important role [ 64 , 65 ]. There are 11,622 genes which are common between the CTD KB and the experimental gene expression data set so we use only these.…”
Section: Knowledge Basementioning
confidence: 99%
“…It achieved better results compared with other document-level relation extraction owing to capturing more complete semantic information of entities. Meanwhile, Chen et al 16 leveraged reading comprehension and prior knowledge for biomedical relation extraction. Their methods achieved better performance compared with other methods because of the novel framework and supplementary prior knowledge.…”
Section: Introductionmentioning
confidence: 99%